Analisis Strategi Penelusuran Informasi di Perpustakaan pada Mahasiswa Tingkat Akhir FIS UINSU - Husein, Zul Fikar; Purwaningtyas, Franindya; Hasibuan, Imam Azhari (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
In general, one of the final tasks of students who want to earn a bachelor's degree is to compile scientific papers or what is commonly called a thesis. Writing thesis, students are required to have independence in the process through the guidance process carried out by the supervisor. The process of writing a thesis requires adequate information support as a source of writing. The research method used in this research is a qualitative research method to describe the nature of the problem under investigation. Sulistyo-Basuki (2006: 78) describes qualitative research intending to get a complete reflection of things for the thoughts of people being watched. This study resulted in final year students of the faculty of social sciences at the UINSU Library. Based on the results of the discussions that have been carried out, seven information search strategies were found in this study. That is Ellis' information seeking behavior strategy. Keywords: Behavior, Information Retrieval, Final Year Student